"Not to Disclose Information Sources": Journalistic Privilege Under Article 19 of ICCPR. Issue 4 (2nd October 2017) - Carter, Edward L.
Abstract : International law took a significant step in recent years toward protection of journalists' sources and newsgathering processes. The international law journalistic privilege previously had been upheld by international tribunals, but it was not until 2011 that the United Nations Human Rights Committee adopted an interpretation of freedom of expression that included journalistic privilege. The presence of the privilege within freedom of expression, as recognized in Article 19 of the International Covenant on Civil and Political Rights, is important for several reasons. As part of freedom of expression, the privilege may not be overcome without a showing of necessity and proportionality, is not subject to a margin of appreciation, and is entitled to full realization by the 168 nations that have signed and ratified ICCPR.